Character Education : Direction and Priority for National Character Development in Indonesia - Sakban, Abdul; Sundawa, Dadang (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to analyze how national character development is implemented and its direction, goals, and top priorities in Indonesia. This study used the systematic literature review method with a qualitative approach. Fifteen reputable national journal (Sinta) articles and ten reputable international journal (Scopus) articles were looked at for 25 pieces. The data analysis technique used in this research was thematic analysis. Thematic analysis is one way to identify patterns and find themes through the researchers’ data. The results of this study showed that Indonesians developed their national character by getting used to participating in leisure and intra-curricular activities and learning. The direction of building a solid national identity was done in three stages. The consolidation stage focuses on ensuring people understand the Pancasila philosophy, the stabilization stage in various subjects, curriculum and school, family and community participation, and the development stage to increase the inauguration of Pancasila ideology-based curriculum. The most crucial part of building national character was ensuring kids grow up to be good, tolerant, and creative citizens, work together, and have integrity and a global outlook.